Предмет: Математика,
автор: Аноним
2 5. Упростите выражение х² + 9-(х+3)².
jekadva:
= -6x
Ответы
Автор ответа:
1
Ответ:вот
Пошаговое объяснение:
Приложения:
Автор ответа:
0
Ответ:
В решении.
Пошаговое объяснение:
2 5. Упростите выражение х² + 9-(х+3)².
х² + 9 - (х + 3)² =
= х² + 9 - (х² + 6х + 9) =
= х² + 9 - х² - 6х - 9 =
= -6х.
Похожие вопросы
Предмет: Английский язык,
автор: ali8080Ali80
Предмет: Русский язык,
автор: вика844
Предмет: Русский язык,
автор: Романик08
Предмет: Литература,
автор: vladisden
Предмет: Химия,
автор: Книголюбитель